Transformation of educational systems in wartime conditions: prospects for reformation - Ponomarova, Galina; Kharkivska, Alla; Petrychenko, Larisa (My University, 2024)
The monograph highlights transformational processes in the education system under martial law. It substantiates applied aspects of digitalization, distance learning, and the integration of inclusive education in all levels of education, in particular in the process of professional training of future specialists for work in today's conditions, and readiness for further active professional activity. The scientific publication may be useful to scientists, teachers, doctoral students, postgraduate students, higher education students, as well as those interested in the modernization of the educational process under martial law.
Transformation of educational systems in wartime conditions: prospects for reformation: international collective monograph / edited by G. F. Ponomarova, A.A. Kharkivska, L.O. Petrychenko and other; Municipal Establishment «Kharkiv Humanitarian Pedagogical Academy» of Kharkiv Regional Council. – Publishing house OKTAN PRINT s.r.o., 2024. – 531 p.
Keywords: підготовка фахівців у закладах вищої освіти в умовах воєнного стану, академічна мобільність здобувачів вищої освіти, духовно-моральне виховання, soft skills, навчально-пізнавальна мотивація особистості, використання цифрових технологій ЗВО, діджиталізація освіти під час війни цифрова трансформація в системі вищої освіти України; training of specialists in higher education institutions under martial law, academic mobility of higher education applicants, spiritual and moral education, soft skills, educational and cognitive motivation of the individual, use of digital technologies in higher education institutions, digitalization of education during war, digital transformation in the higher education system of Ukraine